A multi-analytical approach to understand El Alto-Ancasti's painted pottery (north-western Argentina): Non-invasive and micro-invasive analyses of vessel's paintings from El Taco 19 - Gheco, Lucas Ignacio; Tascon, Marcos; Barot, Carlos Ariel; Zucchi, Victoria; Quesada, Marcos Nicolás; Gastaldi, Marcos Roman; Halac, Emilia Beatriz; Álvarez, Rodrigo; Marte, Fernando (Wiley Blackwell Publishing, Inc, 2023)
Fil: Gheco, Lucas Ignacio. Consejo Nacional de Investigaciones Cientificas y Tecnicas. Centro Cientifico Tecnologico Conicet Noa Sur. Instituto Regional de Estudios Socio-culturales. - Universidad Nacional de Catamarca. Instituto Regional de Estudios Socio-culturales.; Argentina